2019
DOI: 10.1016/j.jsxm.2019.11.266
|View full text |Cite
|
Sign up to set email alerts
|

Self-Compassion, Emotion Regulation, and Female Sexual Pain: A Comparative Exploratory Analysis

Abstract: Introduction Sexual pain is a multideterminate phenomenon, resulting from the interplay between biopsychosocial dimensions. Research suggests that self-compassion plays a protective role on mental health through the enablement of adaptive emotion regulation strategies and that they both contribute to ease chronic pain experience. However, little is known about the role played by self-compassion and emotion regulation on female sexual pain. Aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…However, a 25% of cases can be asymptomatic which may be related to different factors with no clear or consistent patterns found [35]. Chronic pelvic pain may also be related to psychological dysfunction, anxiety and depression, decreased levels of self-compassion and emotional regulation, a history of sexual abuse, previous surgery, and urinary or digestive alterations [36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…However, a 25% of cases can be asymptomatic which may be related to different factors with no clear or consistent patterns found [35]. Chronic pelvic pain may also be related to psychological dysfunction, anxiety and depression, decreased levels of self-compassion and emotional regulation, a history of sexual abuse, previous surgery, and urinary or digestive alterations [36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the self-compassion scale used in this study as it conceptualised and measured compassion related to general mental health difficulties rather than compassion focussed on sexual problems. More recently, Vasconcelos et al (2020) found that cis women with sexual pain or sexual problems reported lower self-compassion and more difficulties with emotional regulation compared to women without these problems.…”
Section: Pain With Penetrative Sexmentioning
confidence: 99%
“…Moreover, lower levels of psychological distress (i.e., depression and anxiety) and greater intimate relationship satisfaction in women with sexual pain and their male partners were associated with self-compassion [ 32 ]. Women with sexual pain were also more likely to report lower levels of self-compassion [ 34 ].…”
Section: Introductionmentioning
confidence: 99%